2004
DOI: 10.1097/00004647-200405000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vascular Reactivity of Isolated Rat Middle Cerebral Artery after Cortical Spreading Depression in Vivo

Abstract: Cortical spreading depression (CSD) is accompanied by hyperemia followed by long-lasting hypoperfusion and impaired cerebrovascular reactivity. The authors show that vasodilation to extraluminal acidosis (pH 7.0) and increased concentrations of extraluminal potassium (12, 20, 40 mmol/L) was significantly reduced in isolated rat middle cerebral arteries after CSD in vivo before the artery was isolated, compared with sham-operated controls. Application of 80-mmol/L potassium induced vasoconstriction after CSD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(43 reference statements)
0
21
0
Order By: Relevance
“…Most previous studies support a biphasic hemodynamic change in SD, with a large hyperperfusion shortly after the DC shift followed by a long-lasting hypoperfusion (Goadsby, 1992;Lacombe et al, 1992;Seitz et al, 2004). Some studies also reported that, before the hyperemic phase, there is a transient hypoperfusion (Dreier et al, 2001;Ayata et al, 2004;Tomita et al, 2005).…”
Section: Discussionmentioning
confidence: 77%
“…Most previous studies support a biphasic hemodynamic change in SD, with a large hyperperfusion shortly after the DC shift followed by a long-lasting hypoperfusion (Goadsby, 1992;Lacombe et al, 1992;Seitz et al, 2004). Some studies also reported that, before the hyperemic phase, there is a transient hypoperfusion (Dreier et al, 2001;Ayata et al, 2004;Tomita et al, 2005).…”
Section: Discussionmentioning
confidence: 77%
“…Other experimental studies have shown that CSD is followed by long-lasting hypoperfusion and impaired cerebrovascular reactivity (6). Regulation impairment is confined to the area of the oligoaemia, suggesting that blood flow variations are caused by changes in local metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…Because solutions were applied locally onto the pial arterioles, diminished reactivity was likely due to changes within the vessels, rather than the parenchyma. Indeed, isolated vessels harvested after they were exposed to an SD in situ showed much diminished reactivity to pH and [K ϩ ] o changes (415). Even the response to the direct vasodilator papaverine appeared to be diminished after an SD in one study (130), although responses to acetylcholine, CGRP, NMDA, K ATP channel opener aprikalim, and adenylate cyclase activator forskolin were reportedly preserved after SD in rabbits (46, 80), suggesting that the vasomotor paralysis may not apply to all species or mediators.…”
Section: Impaired Cerebrovascular Reactivity After Spreading Deprmentioning
confidence: 99%